An efficient and thickness insensitive cathode interface material for high performance inverted perovskite solar cells with 17.27% efficiency. Issue 24 (1st June 2017) - Peng, Sen; Miao, Jingsheng; Murtaza, Imran; Zhao, Liang; Hu, Zhao; Liu, Ming; Yang, Tingbin; Liang, Yongye; Meng, Hong; Huang, Wei
Abstract : A thickness insensitive water/alcohol soluble small molecular, PN6, exhibits high electron mobility with deep LUMO energy level, and effectively decrease the work function of the cathode. Those properties significantly enhance the power conversion efficiency from 8.73% (control cell) to 17.27%. Abstract : In inverted planar heterojunction (PHJ) perovskite solar cells (PSCs), the interface layer between the electron transporting layer and the cathode plays a very important role in achieving high power efficiency. Herein, we present the synthesis of a new water/alcohol soluble small molecular cationic compound based on the naphthalene diimide functionalized pyridinium salt, N, N ′-bis(1- n -hexylpyridinium-4-ylmethyl)-1, 4, 5, 8-naphthalenetetracarboxydiimide (PN6). PN6 exhibits a large band gap (2.95 eV), high electron mobility (7.1 × 10 −5 cm 2 V −1 s −1 ), deep LUMO energy level (−4.07 eV) and can easily form highly transparent thin films. By introducing it as a cathode interface layer in PHJ PSCs, PN6 can effectively decrease the work function of the cathode, boosting all the photovoltaic parameters of the fabricated devices. By using PN6 in the ITO/NiO x /perovskite/PC61BM/PN6/Ag device structure, a power conversion efficiency (PCE) of 17.27% is obtained. Moreover, it is observed that the performance of PHJ PSCs with the PN6 interface layer is insensitive to the interlayer thickness and even at a thickness of 30 nm; the PCE of the device can still reach up to 15.37%, which makes it compatible with large-area roll-to-roll processing technology. These results demonstrate that the naphthalene diimide functionalized pyridinium salt can be a new category of water/alcohol soluble cathode interface material for high performance PHJ PSCs.